Depression and its Association with Insomnia among Geriatric Population of Selected Slums of Bankura Municipality, West Bengal - Atanu Biswas; Gourab Biswas; Sonali Sain; Manisha Sarkar (Medsci Publications, 2024)
Background: While depression is a major health concern among older people, sleep disorders are also very common among them and often persist simultaneously. The study was conducted to assess the prevalence of depression and insomnia, and any correlation of association between them, in the geriatric people living in study area. Methodology: A cross-sectional analytical study was conducted among 186 older people living in three selected slums of Bankura Municipality, West Bengal, India. A pre-tested, structured interviewer-administered-questionnaire including Geriatric Depression Scale-Short form and Insomnia Severity Index were used for data collection. Results: The prevalence of geriatric depression and insomnia in the study setting were 54.3% and 37.6% respectively. While illiteracy, complete financial dependency and taking sedative were associated with geriatric depression, history of smoking was associated with insomnia among participants. Geriatric depression was significantly associated with insomnia. There was statistically significant positive correlation between GDS-S score and ISI score. Conclusions: A significant proportion of elderly population suffers from depressive disorders and sleep disorders. Early detection and management of these conditions will provide the society with healthy 'senior citizens.